EC-ElGamal and Genetic Algorithm based Enhancement for Lightweight Scalable Blockchain in IoT domain - Guruprakash, J; Srinivas, Koppu (IEEE access, 2020)
Security, data privacy and decentralization are significant challenges in the Internet of Things (IoT) domain. These challenges are inherited attribute of another emerging technology, Blockchain. This enforced convergence of IoT and Blockchain, attracting researchers to study on the effective use of Blockchain's strength to solve the challenges of IoT. Rapid IoT adoption requires standardization and mature solution on security, data protection for compliance and performance for commercialization. These demands made a surge in variant blockchain flavours and combinations catering to different problems, and one such is Lightweight Scalable Blockchain (LSB). LSB had considerable caveats that require improvement for better adoption in the IoT domain. This paper focuses on encrypting transaction transmission, improving transaction flow, block validation, hash quality, hash rate and storage cost to improvise security and performance. The experimental evaluation is demonstrated on data from the temperature sensor to showcase superior applicability of the proposed work in the IoT domain. Implementation and result comparison with conventional LSB proves, the following achievements 1) An additional layer of transaction encryption using hybrid Elliptic Curve ElGamal (EC-ElGamal) method increases the security of the transmitted transaction for security enhancement. 2) Obtained 20% reduction in transaction processing time, 22% reduction on block validation processing time, 53% improvement on the hash operation and quality with an overall 7% saving on the storage cost thereby increased the overall performance.